The Effect of Transformational Leadership Style and The Work Environment on Employee Performance at Angkasa Notebook Trading Enterprise in Bandar Lampung - Felix Jasarta; M. Oktavianur (International Journal of Economics, Business and Innovation Research, 2026)
This study examines the effect of transformational leadership style and the work environment on employee performance at Angkasa Notebook Trading Enterprise in Bandar Lampung City. A quantitative survey approach was employed, involving all 33 employees as the research sample through a saturated sampling technique. Data were collected using Likert-scale questionnaires and analyzed using multiple linear regression with SPSS. The findings reveal that transformational leadership style and the work environment each have a positive and significant effect on employee performance. Simultaneously, both variables significantly influence employee performance, with a coefficient of determination of 52.3%. These results highlight the importance of effective transformational leadership and a conducive work environment in enhancing employee performance in small and medium-sized trading enterprises.